Aromatase is a direct target of FOXL2: C134W in granulosa cell tumors via a single highly conserved binding site in the ovarian specific promoter. - Nicholas I Fleming (Public Library of Science (PLoS), 2010)
Background Granulosa cell tumors (GCT) of the ovary often express aromatase and synthesize estrogen, which in turn may influence their progression. Recently a specific point mutation (C134W) in the FOXL2 protein was identified in >94% of adult-type GCT and it is likely to contribute to their development. A number of genes are known to be regulated by FOXL2, including aromatase/CYP19A1, but it is unclear which are direct targets and whether the C134W mutation alters their regulation. Recently, it has been reported that FOXL2 forms a complex with steroidogenic factor 1 (SF-1) which is a known regulator of aromatase in granulosa cells. Methodology/principal findings In this work, the human GCT-derived cell lines KGN and COV434 were heterozygous and wildtype for the FOXL2:C134W mutation, respectively. KGN had abundant FOXL2 mRNA expression but it was not expressed in COV434. Expression of exogenous FOXL2:C134W in COV434 cells induced higher expression of a luciferase reporter for the ovarian specific aromatase promoter, promoter II (PII) (-516bp) than expression of wildtype FOXL2, but did not alter induction of a similar reporter for the steroidogenic acute regulatory protein (StAR) promoter (-1300bp). Co-immunoprecipitation confirmed that FOXL2 bound SF-1 and that it also bound its homologue, liver receptor homologue 1 (LRH-1), however, the C134W mutation did not alter these interactions or induce a selective binding of the proteins. A highly conserved putative binding site for FOXL2 was identified in PII. FOXL2 was demonstrated to bind the site by electrophoretic mobility shift assays (EMSA) and site-directed mutagenesis of this element blocked its differential induction by wildtype FOXL2 and FOXL2:C134W. Conclusions/significance These findings suggest that aromatase is a direct target of FOXL2:C134W in adult-type GCT via a single distinctive and highly conserved binding site in PII and therefore provide insight into the pathogenic mechanism of this mutation.